Enhanced sensitivity of colon tumour cells to natural killer cell cytotoxicity after mild thermal stress is regulated through HSF1-mediated expression of MICA. (30th July 2013) - Dayanc, Baris E.; Bansal, Sanjay; Gure, Ali Osmay; Gollnick, Sandra O.; Repasky, Elizabeth A.
Abstract: Purpose : Previously we showed that mild thermal stress increased natural killer (NK) cell-mediated tumour cytotoxicity and that this could be blocked by anti-NKG2D or anti-MICA (major histolocompatability complex (MHC) class I related chain A) antibodies. Here, we investigated the role of the transcription factor heat shock factor 1 (HSF1) in thermal regulation of MICA expression in tumour cells in vitro and in vivo . Materials and methods : Hyperthermia experiments were conducted in vitro and in mice using a target temperature of 39.5 °C . Apoptotic cells and NK cells in situ were visualised by use of the TUNEL assay or expression of NKp46 respectively. Using Colo205 cells, HSF1 message was blocked utilising siRNA while luciferase reporter assays were used to measure the activity of the MICA promoter in vitro . Cell surface MICA was measured by flow cytometry. Results : Following whole body hyperthermia (WBH), tumour tissues showed an increase in NK cells and apoptosis. Mild thermal stress resulted in a transient increase in surface MICA and enhanced NK cytotoxicity of the Colo205 colon cancer cell line. Silencing (mRNA) HSF1 expression in Colo205 cells prevented the thermal enhancement of MICA message and surface protein levels, with partial loss of thermally enhanced NK cytotoxicity. Mutations of the HSF1 binding site on the MICA promoter implicated HSF1 in the thermal enhancement of MICA. Some, but not all, patient-derived colon tumour derived xenografts also exhibited an enhanced MICA message expression after WBH. Conclusions : Up-regulation of MICA expression in Colo205 cells and enhanced sensitivity to NK cell killing following mild thermal stress is dependent upon HSF1.